Abundance and diversity of soil mites of fragmented habitats in a biosphere reserve in Southern Nigeria - Badejo, Mosadoluwa Adetola; Adams, Buny Amin Ola (Pesquisa Agropecuaria Brasileira, 2000)
Soil samples were collected from the top 7.5 cm of soil in a Strict Natural Reserve (SNR), a surrounding buffer zone, a cassava farm and matured plantations of Gmelina, teak, and pine, so as to determine if plantation establishment and intensive cultivation affect the density and diversity of soil mites. Altogether, 41 taxonomic groups of mites were identified. The diversity and densities of mites in within the SNR, the buffer zone and the Gmelina were more than the diversity and densities in the cassava farm, teak and pine plantations. Each plantation had its own unique community structure which was different from the community structure in the SNR plot. The SNR plot and Gmelina were dominated by detritivorous cryptostigmatid mites unlike teak and pine which were dominated by predatory mesostigmatid and prostigmatid mites respectively. Low cryptostigmatid mite densities in the plantations and cassava farm were seen as a consequence of low fertility status of the soil, the evidence of which was revealed by soil pH and organic matter data.